The Effect of Phytosterols and Fatty Acids of Pistachio (Pistacia vera) Oil on Spermatogenesis and Histological Testis Changes in Wistar Adult Male Rats: The effect of pistachio oil on spermatogenesis - Khanamani Falahati-pour, Soudeh; Pourmasumi, Soheila; Mohamadi, Maryam; Taghipour, Zahra; Mohammadinasab, Mohammad Reza; Sajadian, Mojtaba; Ayoobi, Fatemeh; Dini, Ali; Ahmadi, Zahra; Khanamani Falahatipour, Sakineh; Nazari, Alireza (Urology Journal, 2021)
Purpose: Oilseeds and their related products are known to have various bioactive and health-promoting ingredients. In this research, we investigated the effects of phytosterols and fatty acids of Pistacia vera on spermatogenesis process and testis histological changes in Wistar male rats for the first time. Materials and Methods: A total number of 64 adult male Wistar rats were divided randomly into eight groups including one control group, and seven test groups. Test groups received phytosterols, fatty acids, and pistachio oil orally for 30 days. Then, LH, FSH, and serum testosterone levels were determined. Also, the spermatogenesis process and changes in testicular tissue in rats were investigated. Results: The results of this research suggest that phytosterols in doses of 10 and 50 mg/kg reduce the spermatogenesis process. Fatty acid in a low dose of 10 mg/kg increases spermatogenesis, but when a high dose of 50 mg/kg was used, it harmed the spermatogenesis process. When low levels of phytosterols and fatty acids are used simultaneously in dose 5 mg/kg, improvement in spermatogenesis process is observed but when these were used together in the dose of 25 mg/kg, the spermatogenesis process was disrupted. Using pistachio oil alone also improved spermatogenesis process. Conclusion: It seems that phytosterols reduce spermatogenesis at high and low doses, while fatty acids increase spermatogenesis when used in low doses and reduce this process when used in high doses. The use of fatty acids extracted from pistachios to treat infertility in men seems hopeful.